A prevention model against addiction for migrant youth: Bavul - Yaylacı, Fatıma Tuba; Gülerce, Hakan; Nişancı, Aslıhan; Gülerce, Rukiye; Akpınar, Burcu; Fidan, Merve; Korkmaz, Zeynep; Çelebi, Afra Sevde; Turan, Ege (Addicta: The Turkish Journal on Addictions, 2026)
Migration-related stress, discrimination, and disrupted support systems increase vulnerability to addictive behaviors among youth. Despite this, few prevention programs address the intersection of migration, trauma, and identity development in culturally responsive ways. This article presents a prevention model against addiction for migrant youth, Bavul, grounded in a trauma-informed, rights-based, and youth-centered approach and built on a strengths-based framework. Designed to be low in language demand and high in experiential participation, the model integrates resilience-building, the normalization of stress responses, life skills development, identity formation, critical thinking, and well-being through accessible, youth-friendly coping and decision-making strategies. Structured in eight modules, the model combines interactive learning, reflective storytelling, and creative group activities. Core principles include non-judgmental facilitation, cultural sensitivity, and empowerment through agency. The article discusses Bavul model’s contribution to preventive practice within multicultural contexts and its potential to inform future prevention and mental health frameworks targeting migrant youth.
Keywords: adolescent; migrants; addiction; prevention; psychological resilience; youth empowerment